2019
DOI: 10.3390/cells8060517
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Controls Murine Chronic Intestinal Inflammation by Modulating Immune Cell Functions and Gut Microbiota Composition

Abstract: Different gastrointestinal disorders, including inflammatory bowel diseases (IBD), have been linked to alterations of the gut microbiota composition, namely dysbiosis. Fecal microbiota transplantation (FMT) is considered an encouraging therapeutic approach for ulcerative colitis patients, mostly as a consequence of normobiosis restoration. We recently showed that therapeutic effects of FMT during acute experimental colitis are linked to functional modulation of the mucosal immune system and of the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 66 publications
(108 reference statements)
4
51
0
Order By: Relevance
“…Phenotypically, FMT-treated mice show lower percentages of CD 8+ T and CD 4+ T cells, which express the cytotoxicity-related molecule CD107a. This further supports the observation of a decrease in the pro-inflammatory phenotype of colonic T cells in mice treated with FMT (Burrello et al, 2019).…”
Section: T-cell Populationssupporting
confidence: 89%
See 1 more Smart Citation
“…Phenotypically, FMT-treated mice show lower percentages of CD 8+ T and CD 4+ T cells, which express the cytotoxicity-related molecule CD107a. This further supports the observation of a decrease in the pro-inflammatory phenotype of colonic T cells in mice treated with FMT (Burrello et al, 2019).…”
Section: T-cell Populationssupporting
confidence: 89%
“…It is not known if tissue impairment is caused by abnormal immune responses to normal microbiota or by a normal immune response to abnormal microbiota or if dysbiosis constitutes a cause or outcome of IBD (Sheehan et al, 2015;Ni et al, 2017). FMT is considered a promising therapeutic methodology for IBD patients, primarily to achieve outcomes of intestinal microbial restoration (Burrello et al, 2019). FMT can increase the diversity of intestinal microorganisms, together with rebuilding the immune system and maintaining the balance of intestinal microecology.…”
Section: Immunomodulatory Effects and Mechanisms Of Fmtmentioning
confidence: 99%
“…Recent studies on both acute and chronic experimental colitis showed that the therapeutic effects of FMT are linked to functional modulation of the mucosal immune system and of the gut microbiota composition. 94,95 Specifically, expression of pro-inflammatory genes, antimicrobial peptides, and mucins were observed to decrease in animals receiving the treatment.…”
Section: Microbiotamentioning
confidence: 99%
“…Combining FMT and antibiotics contributed to the microbiological improvement of intestinal dysbiosis in UC patients [23]. Previous study found the microbiota could alleviate murine chronic intestinal inflammation through modulating immune cell functions in terms of FMT [24].…”
Section: Introductionmentioning
confidence: 96%